2018
DOI: 10.1111/ijpo.12486
|View full text |Cite
|
Sign up to set email alerts
|

Initial evidence for hypothalamic gliosis in children with obesity by quantitative T2 MRI and implications for blood oxygen‐level dependent response to glucose ingestion

Abstract: Summary Objective In adults, hypothalamic gliosis has been documented using quantitative T2 neuroimaging, whereas functional magnetic resonance imaging (fMRI) has shown a defective hypothalamic response to nutrients. No studies have yet evaluated these hypothalamic abnormalities in children with obesity. Methods Children with obesity and lean controls underwent quantitative MRI measuring T2 relaxation time, along with continuous hypothalamic fMRI acquisition to evaluate early response to glucose ingestion. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
42
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 39 publications
(108 reference statements)
10
42
1
Order By: Relevance
“…Notably, adults with obesity, relative to those with healthy weight, have increased T2‐weighted signal intensity in the hypothalamus, indicative of gliosis (25). Likewise, in children with obesity, increased T2‐weighted signal intensity (suggesting hypothalamic gliosis) is positively associated with adiposity (30). Moreover, histological studies specifically examining hippocampal tissue have shown that different types of hippocampal tissue alterations can lead to either increased T2‐weighted signal intensity (i.e., hippocampal sclerosis and gliosis) or decreased T2‐weighted signal intensity (i.e., increased vacuolation) within this region (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, adults with obesity, relative to those with healthy weight, have increased T2‐weighted signal intensity in the hypothalamus, indicative of gliosis (25). Likewise, in children with obesity, increased T2‐weighted signal intensity (suggesting hypothalamic gliosis) is positively associated with adiposity (30). Moreover, histological studies specifically examining hippocampal tissue have shown that different types of hippocampal tissue alterations can lead to either increased T2‐weighted signal intensity (i.e., hippocampal sclerosis and gliosis) or decreased T2‐weighted signal intensity (i.e., increased vacuolation) within this region (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using functional magnetic resonance imaging (fMRI), obese individuals showed different hypothalamic functional activity compared with lean individuals after glucose consumption (Van De Sande‐Lee et al, 2011). Obese children were verified with hypothalamic gliosis, which was associated with alterations in the glucose‐stimulated hypothalamic functional response (Sewaybricker et al, 2019). After bariatric surgery, changes in hypothalamus activity after glucose intake were observed in fMRI analysis, bringing these responses closer to the lean group (Van De Sande‐Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Besides adiposity, gliosis is another acquired factor that could potentially influence connectivity via effects on hypothalamic brain structure(17). Hypothalamic gliosis was first identified in diet-induced obese rodents in the arcuate nucleus of the MBH(17) and has been detected in humans by quantitative MRI methods in association with obesity in both adults(17,19,20) and children(22). MBH gliosis correlates positively with BMI(19) and visceral fat content(22).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic gliosis was first identified in diet-induced obese rodents in the arcuate nucleus of the MBH(17) and has been detected in humans by quantitative MRI methods in association with obesity in both adults(17,19,20) and children(22). MBH gliosis correlates positively with BMI(19) and visceral fat content(22). The data herein suggest that MBH gliosis, independent of obesity, might affect meal-related response in SN connectivity, but not necessarily basal connectivity.…”
Section: Discussionmentioning
confidence: 99%